Use of Balanced Scorecard for Enterprise Competitiveness Assessment - FAIZOVA, Svitlana Oleksandrivna; IVANOVA, Maryna Illivna; FAIZOVA, Olha Latyfivna; SMIESOVA, Viktoriia Leonidovna; PARSHYNA, Olena Anatoliyivna; ZAVHORODNIA, Olena Oleksandrivna (Journal of Advanced Research in Law and Economics, 2020)
The problem of defining the prospects, opportunities, limitations and methodological format of assessing the competitiveness of an enterprise in a transitive economy using the Balanced Scorecard (BSC) concept has been considered. The relevance of the issue is due, on the one hand, to global trends in innovative development, and on the other hand, to the incompliance of performance of the post-socialist industrial enterprises with the characteristics of innovative development. The creation of mechanisms for improving the enterprise’s competitiveness and its appropriate assessment based on the use of advanced management practices and technologies is becoming increasingly relevant. The purpose of study is to improve methodological approach to the BSC-based assessment of competitiveness of a value-oriented enterprise, and to substantiate the prospects of effective integration of the BSC into the existing enterprise management system . This research paper justifies the possibility of using various methodological forms, including the simplest ones, of the Balanced Scorecard, which features a transformational nature, in the process of forming a balanced strategic management of enterprise. Methodical approach has been proposed for identification of the enterprise strategy directed at increase of its market value and strategic competitiveness. Matrix analysis was applied to assess the enterprise performance indicators; it revealed a relationship between the enterprise's competitive position and class of its innovation BSC-based strategies. To assess the enterprise’s competitiveness, an integral index of its investment attractiveness has been proposed, and to assess the class of the enterprise innovative strategies, an integral index of the enterprise innovations was calculated. The proposed methodological approach was used to perform expert sampling within the frame of indicators for determining the investment attractiveness and innovativeness of a metallurgical enterprise by the criteria of strategic orientation, efficiency and functionality. The study has analyzed the experience gained by the leading enterprises of Ukraine’s metallurgical complex in using BSC in a limited methodological format as a tool for identifying the strategy of an enterprise, assessing its competitiveness, innovativeness and investment attractiveness. The result of the study was the conclusion about the possibility of applying the simplest Balanced Scorecard forms as a catalyst for innovative transformations and developing balanced enterprise management in transition economies.